POTENTIAL USE OF VASCULAR ENDEMIC PLANTS AS A SOURCE OF NEW MEDICINES - Redzic, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The biodiversity of W Balkan includes 7,000 vascular plants. In ethnobotany of this region people use approximately 960 plant species in traditional human and veterinarian phytotherapy and nutrition [1,2]. Except of more common plants therea are a lot of endemic and relic vascular plant species as a potentials for the production of new medicines through edvanced biotehnology and genetical engeneering [3]. Wester Balkan area are so rich in endemic species. In our investigation more than 579 plant species have been found on the Dinaric Mts. only [4]. Main aims of this presentation is to found of richnees of of medicinal wild flora and to deteriminate their phylogenetic-biochemical relationship with common medicinal plants as well as d, to evaluate biodiversity of the potential medicinal flora and its possibility in terms of new chemical compound’s discoveries and modes of use in contemporary phytotherapy and biotechnology. In order to achieve all planned aims, it has been applied adequate methodology: intensive field research on different vertical profiles, including ethnobotanical interviews, followed at the end by comparative taxonomic-biochemical method. Among plants that could be potentially significant in terms of the pharmacology and pharmacy it was detected 450 endemic species of Dinaric Mts. and other parts of W Balkan. The most significant new resources are contained within endemic genera: Pinus (Pinaceae), Drypis, Dianthus, Minuartia, Saponaria, Silene (Caryophyllaceae), Ranunculus, Anemone, Pulsatilla, Aquilegia, Helleborus (Ranunculaceae), Berteroa, Aubretia, Malkolmia, Alyssum, Cardamine (Brassicaceae), Potentilla, Sibireja, Geum, Dryas (Rosaceae), Astragalus, Genista, Oxytropis, Anthyllis (Fabaceae) Athamanta, Eryngium, Pancicia, Peucedanum, Seseli, Bunium (Apiaceae), Acinos, Micromeria, Salvia, Satureja, Stachys, Teucrium, Thymus, Scutellaria (Labiatae), Euphrasia, Pedicularis, Scrophularia (Scrophulariaceae), Veronica, Plantago (Plantaginaceae), Achillea, Amphoricarpos, Centaurea, Crepis, Leucathemum, Senecio, Doronicum (Asteraceae), Lilium, Chouardia, Allium (Liliaceae) and others. Those plants are potentiall sources of new metabolites, such as alcaloids, heterozides, saponins, essential oils, tannins, carbohydrates, proteins as well as other secondary and primary metabolites. References: 1.Redzic, S.(2006)Proc.1st IFOAM Intern. Conf. Organic Wild Production, 117-141. 2. Redzic, SJ. (2006)Ecol.Food & Nutr. 45, 3,189-232. 3.Redzic, S.(2008) Planta Medica 74(9):1143-1144. 4. Redzic, S. (2007) Planta Medica 73(9): 1013-1013.